2006
DOI: 10.1002/chem.200501091
|View full text |Cite
|
Sign up to set email alerts
|

Organotin Perfluorooctanesulfonates as Air‐Stable Lewis Acid Catalysts: Synthesis, Characterization, and Catalysis

Abstract: The reactions of 1,3-dichloro-1,1,3,3-tetrabutyldistannoxane and dialkyltin dihalides with silver perfluorooctanesulfonate provided the corresponding sulfonates as hydrates. The number of water molecules (n) of hydration was dependent on the conditions. The distannoxane derivative was identified as n from 0.5 to 6, while in the hydrated mononuclear species and DMSO complexes n varied widely from 4 to 13. 119Sn NMR spectroscopy and conductivity measurements indicated the ionic dissociation of these compounds in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 38 publications
0
31
0
Order By: Relevance
“…TMSOTf [32] and Cp 2 Ti(OTf) 2 [40] show high catalytic activity but they are known to be unstable in air (Table 5, Entries 3,4). The reference catalysts of Sc(OTf) 3 [30], Bi(OTf) 3 [33], Mg(NTf 2 ) 2 [23], I 2 [38] and DMAP [5] (highly toxic; e.g., intravenous LD50 in the rat: 56 mg/ kg) [23], and AgOSO 2 C 8 F 17 [43], show lower catalytic activity than Cp 2 Ti(OSO 2 C 8 F 17 ) 2 (Table 5, Entries 5-9). Furthermore, these catalysts are hydrolytic in air and liberate CF 3 SO 3 H which has been considered as powerful catalyst by Hollis et al [42].…”
Section: Acetylation Of 2-phenylethanol With Acetic Anhydride Catalyzmentioning
confidence: 99%
See 1 more Smart Citation
“…TMSOTf [32] and Cp 2 Ti(OTf) 2 [40] show high catalytic activity but they are known to be unstable in air (Table 5, Entries 3,4). The reference catalysts of Sc(OTf) 3 [30], Bi(OTf) 3 [33], Mg(NTf 2 ) 2 [23], I 2 [38] and DMAP [5] (highly toxic; e.g., intravenous LD50 in the rat: 56 mg/ kg) [23], and AgOSO 2 C 8 F 17 [43], show lower catalytic activity than Cp 2 Ti(OSO 2 C 8 F 17 ) 2 (Table 5, Entries 5-9). Furthermore, these catalysts are hydrolytic in air and liberate CF 3 SO 3 H which has been considered as powerful catalyst by Hollis et al [42].…”
Section: Acetylation Of 2-phenylethanol With Acetic Anhydride Catalyzmentioning
confidence: 99%
“…Due to their hydrophobic and electron-withdrawing features, long perfluoroalkanes have been used to produce metal perfluoroalkanesulfonates that show strong Lewis acidity and good water tolerance. Organotin perfluorooctanesulfonate was found to be air-stable and water-tolerant, in sharp contrast to the corresponding organotin triflates that are highly hygroscopic [43]. With such understanding, we prepared novel metallocene complexes: Cp 2 M(OSO 2 of alcohols, phenols, thiols, and amines under solvent-free conditions, and found that this approach has merits such as operational simplicity, solvent-free condition, mild reaction conditions, and catalyst recyclability [47].…”
Section: Introductionmentioning
confidence: 97%
“…The same compound also effectively mediates the Robinson annulations [6]. Recently, Otera used structurally similar organotin(IV) perfluorooctanesulfonates as catalysts for various carbonecarbon bond-forming reactions [7]. To the best of our knowledge, there are no organotin(IV) triflates bearing the L CN ligand described in the literature.…”
Section: Introductionmentioning
confidence: 97%
“…They have been successfully used in acetylation [17], deacetylation reactions [19] and for the production of diphenyl carbonate [15]. They have also been involved in various carbon bond forming reactions such as Mukaiyama-aldol as well as Mukaiyama-Michael reactions and allylations of aldehydes [20]. In some cases, [10,12,17,18] where the tin atoms bear two organic groups, they have been isolated as dications that are dissociated in solution.…”
Section: Introductionmentioning
confidence: 99%